2009
DOI: 10.1103/physrevd.79.041902
|View full text |Cite
|
Sign up to set email alerts
|

Fermion localization in a generalized Randall-Sundrum model

Abstract: A generalized two-brane Randall-Sundrum warped braneworld model admits of solutions of the warp factor for both positive or negative cosmological constant on the visible 3-brane which can resolve the naturalness problem in connection with the fine tuning of Higgs mass in the standard model of elementary particles. To explore the location of the standard model fermions in such a generalized warped model, we, in this work, determine the dependence of the localization profile of a bulk fermion on the brane cosmol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 33 publications
(32 reference statements)
6
29
2
Order By: Relevance
“…Some of these are formulated by placing the standard model fields inside the bulk. For these models the localization property of a bulk fermion field on the brane [48][49][50][51][52][53][54][55] has been a subject of great interest to explore the chiral nature of massless fermions and also the hierarchical masses of fermions among different generations [54]. In this context, it is observed that the overlap of the bulk fermion wave function on our visible brane plays a crucial role in determining the effective radion-fermion coupling, which in turn determines the phenomenology of the radion with brane matter fields.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these are formulated by placing the standard model fields inside the bulk. For these models the localization property of a bulk fermion field on the brane [48][49][50][51][52][53][54][55] has been a subject of great interest to explore the chiral nature of massless fermions and also the hierarchical masses of fermions among different generations [54]. In this context, it is observed that the overlap of the bulk fermion wave function on our visible brane plays a crucial role in determining the effective radion-fermion coupling, which in turn determines the phenomenology of the radion with brane matter fields.…”
Section: Introductionmentioning
confidence: 99%
“…But the visible brane in RS model have a negative tension which is intrinsically unstable. Furthermore the visible 3-brane (four-dimensional spacetime) has zero cosmological constant, which is not consistent with presently observed small value [11,12]. Such a braneworld model has been widely studied.…”
Section: Introductionmentioning
confidence: 84%
“…In the present paper we discuss the time-evolving Schrödinger version of the WDW equation for the five dimensional k = 0-FRW Universe, whose warp factor and scale function are respectively given by (12a) and (13). Even though there is an active debate on how one is able to include in the theory a time derivative term in the frozen WDW equation, strategies for connecting it to the timedepending Schrödinger equation have been proposed [12].…”
Section: Discussionmentioning
confidence: 99%
“…for a(t) given by (13). This suggests the definition of the "true" Lagrangian (not density or something else)…”
Section: The Quantum Analysismentioning
confidence: 98%
See 1 more Smart Citation